Engineered targeting tLyp-1 exosomes as gene therapy vectors for efficient delivery of siRNA into lung cancer cells - Jing Bai; Jialun Duan; Rui Liu; Yafei Du; Qian Luo; Yinuo Cui; Zhanbo Su; Jiarui Xu; Ying Xie; Wanliang Lu (Elsevier, 2020)
Natural exosomes can express specific proteins and carbohydrate molecules on the surface and hence have demonstrated the great potentials for gene therapy of cancer. However, the use of natural exosomes is restricted by their low transfection efficiency. Here, we report a novel targeting tLyp-1 exosome by gene recombinant engineering for delivery of siRNA to cancer and cancer stem cells. To reach such a purpose, the engineered tLyp-1-lamp2b plasmids were constructed and amplified in Escherichia coli. The tLyp-1-lamp2b plasmids were further used to transfect HEK293T tool cells and the targeting tLyp-1 exosomes were isolated from secretion of the transfected HEK293T cells. Afterwards, the artificially synthesized siRNA was encapsulated into targeting tLyp-1 exosomes by electroporation technology. Finally, the targeting siRNA tLyp-1 exosomes were used to transfect cancer or cancer stem cells. Results showed that the engineered targeting tLyp-1 exosomes had a nanosized structure (approximately 100 nm) and high transfection efficiency into lung cancer and cancer stem cells. The function verifications demonstrated that the targeting siRNA tLyp-1 exosomes were able to knock-down the target gene of cancer cells and to reduce the stemness of cancer stem cells. In conclusion, the targeting tLyp-1 exosomes are successfully engineered, and can be used for gene therapy with a high transfection efficiency. Therefore, the engineered targeting tLyp-1 exosomes offer a promising gene delivery platform for future cancer therapy.